(untitled) (Stavební obzor - Civil Engineering Journal, 2020)
Natural soil in engineering practices is not always considered to bear loads of above structures. In such a way, it is necessary to improve the quality of the soil before any constructions. Tanks are the structures that apply significant load to the beneath soil and they are usually constructed with circular foundations in shape. Seismic loads can apply irremediable damages to the structures and sometimes tanks are the highly important infrastructures during earthquakes. One of the most techniques that has been recently widely used on soft deposits and loose fine-grained soils is stone columns or singular piles. The stone columns increase the strength of loose soils and also decrease settlements induced by applying the loads. In this study, a linear numerical model of the structure-foundation-soil-stone column was simulated using the ABAQUS. Results show that with the increase of the length of stone columns a decrease in settlement occurred, while the increase of length more than a specific threshold had no significant effect to decrease the uplift and settlement.